Labirintos da bola: normatização e práticas do futebol em Feira de Santana (1942-54) - Lázaro, João Pedro Prado Mercês (2015)
This work deals with how the sport was organized in general and particularly football in Feira de Santana in the years 1942 to 1954. These dates back to the year of the creation of Feirense League Land Sports (LFDT) and the invitation to Fluminense de Feira de Santana, Bahia inside the first team to participate in the Bahia championship professional football. Anchored in Pierre Bourdieu's interpretations, we analyze the Folha do Norte newspaper and some laws for the sport, local and national. We found that from this context was set up the sports field in the city of Bahia's interior, where disputed institutions in a systematic way, way over form and the legitimate role of sport in Feira. In the light of Michel Foucault contributions that examine, in an attempt to produce directions for local sport, some equipment sold sports practice ideas in dialogue with a sense of progress, order and discipline. However, seeking to follow the lessons of Walter Benjamin, try reading these official documents against the grain. Thus, we try to identify the waywardness in the execution of this disciplinary power, conflicts and contradictions these actions, when put into practice in the ball game.